THE VISIONARY LEADERSHIP STRATEGY IN ADVANCING EDUCATIONAL INSTITUTIONS - Muhammad Ubaidillah; Ratih Christiana; Akhmad Sahrandi (Universitas Brawijaya, 2019)
Educational institutions need clearer directions for all members of the organization. Organizations need people who are able to set the direction forward, spread it to all members of the organization, direct people to achieve goals, build networks with other institutions, provide incentives, motivate and reward subordinates who excel. People who are able to do such things are called visionary leaders. Therefore, this study aims to analyze the visionary leadership strategy in advancing educational institutions, so as to produce a perfect human being who can answer the challenges of every age. This research method uses a qualitative approach with library research methods. Sources of data obtained from books, research results, journals, or scientific information related to visionary leadership strategies. The results were obtained that visionary leadership was felt as an urgent need for educational institutions, in order to be able to realize an advanced educational institution and to be the center of attention and expectations of the wider community. Visionary leaders have a realistic leadership vision, can be convincing and guide the organization to achieve an ideal of the future that is better than current conditions. Visionary leadership is always consistent and focused on achieving vision, practice is not rigid in facing organizational challenges and opportunities.